2013
DOI: 10.1177/0894439313493979
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of State-of-the-Art Electoral Prediction From Twitter Data

Abstract: Electoral prediction from Twitter data is an appealing research topic. It seems relatively straightforward and the prevailing view is overly optimistic. This is problematic because while simple approaches are assumed to be good enough, core problems are not addressed. Thus, this paper aims to (1) provide a balanced and critical review of the state of the art; (2) cast light on the presume predictive power of Twitter data; and (3) depict a roadmap to push forward the field. Hence, a scheme to characterize Twitt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
180
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(187 citation statements)
references
References 31 publications
1
180
0
6
Order By: Relevance
“…On the one hand, this makes these studies highly popular in that they seemingly offer a fairly straightforward way to measure and predict social, economic, and political phenomena. On the other hand, these studies have been found to be highly vulnerable to replication efforts, indicating that early hopes might be a case of collective overexcitement rather than the hoped-for replacement for more traditional measurement approaches or the prediction of future developments (Gayo-Avello, 2013;Jungherr, Jürgens, & Schoen, 2012;Lazer, Kennedy, King, & Vespignani, 2014;Metaxas, Mustafaraj, & Gayo-Avello, 2011). Here, it is of paramount importance that social science loses its fascination with the proof-of-concept publication model imported from computer science and instead demands sophisticated tests of indicator validation and the theorizing and testing of links between variables ostensibly linked.…”
Section: The Empiricist Challengedmentioning
confidence: 99%
“…On the one hand, this makes these studies highly popular in that they seemingly offer a fairly straightforward way to measure and predict social, economic, and political phenomena. On the other hand, these studies have been found to be highly vulnerable to replication efforts, indicating that early hopes might be a case of collective overexcitement rather than the hoped-for replacement for more traditional measurement approaches or the prediction of future developments (Gayo-Avello, 2013;Jungherr, Jürgens, & Schoen, 2012;Lazer, Kennedy, King, & Vespignani, 2014;Metaxas, Mustafaraj, & Gayo-Avello, 2011). Here, it is of paramount importance that social science loses its fascination with the proof-of-concept publication model imported from computer science and instead demands sophisticated tests of indicator validation and the theorizing and testing of links between variables ostensibly linked.…”
Section: The Empiricist Challengedmentioning
confidence: 99%
“…This is indeed true if one makes inferences about the amount of support for a certain specific policy or candidate, and this is why attempts to use Twitter analysis as a replacement for polling have been extensively criticized (Gayo-Avello, 2013;Jungherr, et al, 2011). Yet, this is less of a concern in our case as we are not interested in obtaining exact estimates of percentages of the population that hold a given opinion.…”
Section: The Second Screen As Remote Co-viewing Place For Debate Andmentioning
confidence: 99%
“…Voting results have been correlated with tweets in the 2009 German elections [53], addressing the counting of the tweets citing the different parties without providing a predictive model, another example can be found in [4]. In [15], sentiment analysis and volume approaches has been used for electoral prediction in the Senate competition which is 1:1, still obtaining correlations in the range of 40-60%.…”
Section: Related Workmentioning
confidence: 99%